Cognitive and cultural proximity between service managers and customers in cross-border regions: knowledge transfer implications. (30th November 2016) - Weidenfeld, Adi; Björk, Peter; Williams, Allan M
ABSTRACT: Knowledge transfer between customers and managers is an important source of new ideas for innovation in the service industries. In cross-border regions, inter-cultural interactions engender but also constrain knowledge transfers between actors even when actors share similar economic and technological knowledge bases. This theme is explored through an analysis of cognitive and cultural proximity between service managers and customers from "the other side" in a European cross-border region where the constituent regions have broadly similar national cultures: Tornio-Haparanda on the border between Finland and Sweden. Semi-structured in-depth interviews with 19 Swedish and Finnish managers of small and micro businesses serving customers from both sides were undertaken to gauge their perceptions of the impact of cultural and cognitive proximity to customers on learning interactions. The study adds to the emerging literature in this field by identifying seven elements of cognitive and cultural proximity including mentality, ways of solving problems, conservatism, shared language, focus on contextualised details, mentality, and use of similar technologies. It is also original for suggesting some the implications for the possible impacts of perceived cultural and cognitive proximity on cross-border knowledge transfer between customers and managers.